The Power of Service Quality Influence on Community Satisfaction: Is Community Satisfaction Influenced By Service Quality? - Risma Ismaya; Inggit Sukmawati Hamdani; Nursahidin Nursahidin (Pelopor Publikasi Akademika, 2024)
The One-Stop Manunggal Administration System known as SAMSAT is committed to providing quality services to all people who are taxpayers through mobile Samsat. Because the service process at the Main Samsat takes time so that it has an impact on taxpayer compliance. This study aims to determine the influence of the quality of Samsat Mobile services on the satisfaction of the people of Cirebon City. Through the use of quantitative methods and primary data, data collection was carried out through the distribution of questionnaires using simple random sampling techniques. The results of the analysis of the T test showed that the quality of service had a significant effect on community satisfaction, with a significance value of 0.000 < 0.05, then there was rejection and acceptance which showed that the quality of the Mobile Samsat service had an effect on community satisfaction. The results of the determination coefficient test showed that the quality of service had an influence of 73%, while the remaining 27% was influenced by other variables that were not studied in this study.